THE URGENT NEED TO AMEND THE INDONESIAN LAW ON CURRENCIES TO FACE THE DIGITAL AGE - Nefi, Arman; Sardjono, Agus (Bank Indonesia, 2022)
This research focuses on Indonesian Law No. 7 of 2011 on Currency. Over the past ten years, information technology has developed so rapidly that it has been necessary to take another look at whether this law is still relevant now and in the near future. The research uses normative legal analysis methods with a conceptual approach, analytical approach, comparative approach across multiple countries, and case studies. The rapid development has left the law behind when addressing violations of the currency law. To eliminate ambiguity and hesitation in the implementation of the use of currency, this law must be amended. It is necessary to establish clear laws on digital money or electronic money (e-money), which is currently only regulated at the level of Bank Indonesia and Bank Indonesia Circular Letter. The use of foreign currency in border markets and places of foreign tourists, money in some places due to technological advances, and about the local wisdom of a society that has a history of using certain goods as currency. Things that develop and are a reality in society should be contained in statutes to settle the law.